Analysis of Gayo horse reproductive performance as a local livestock genetic resource in Aceh Province to characterize reproductive efficiency - Sari, Eka Meutia; Abdullah, Mohd. Agus Nashri; Yoga, Asri; Agung, Nabilah Putroe; Novita, Cut Intan; Ammar, Muhammad; Koesmara, Hendra (Journal of Advanced Veterinary Research, 2025)
This study aimed to determine strategies for future Gayo horse development by examining the reproduction of the Gayo horse breed, which runs in the Gayo highland. The study was conducted in the regencies of Central Aceh, Bener Meriah, Gayo Lues, and Southeast Aceh in Aceh Province. A survey methodology was used. The study sites were selected due to the importance of the Gayo horse as a genetic resource, 112 Gayo horses were used as research samples. Some of the data required for this study were reproductive performance variables such as (1) age at first mating, (2) gestation period, (3) calving interval, and (4) postpartum mating. This study found that Gayo horses have a high reproductive rate. The average age of first mating ranged from 30 to 46 months, with a mean time span of 39.51 ± 84.49 months. Gestation averaged 339.38 ± 7.88 days, with a range of 333 to 347 days. The average calving interval was 425.78 ± 38.15 days, with a range of 370 to 495 days. The average postpartum mating interval was 134.74 ± 23.70 days, with a range of 123-150 days.